The Relationship Between Self-Compassion and Body Dissatisfaction Among Psychology Students at Bhayangkara University Jakarta Raya - Gardyanie Hermawan, Liza (Lafadz Jaya Publisher, 2024)
Feelings of inferiority represent a significant psycho-social issue for individuals, often leading to difficulties in decision-making, hesitancy, a lack of assertiveness, withdrawal, and heightened emotional sensitivity. These challenges are particularly prevalent among adolescents, who frequently compare themselves to others in their environment. Body dissatisfaction emerges when adolescents compare their actual body to an idealized version and struggle to accept their current appearance. One factor influencing body dissatisfaction is self-compassion, which can either mitigate or exacerbate these feelings. This study aims to investigate the relationship between self-compassion and body dissatisfaction among students of the Faculty of Psychology at Bhayangkara University Jakarta Raya. Using convenience sampling, 100 students participated in the study. The findings indicate a significant negative correlation between self-compassion and body dissatisfaction, with a correlation coefficient of r = -0.803*** and p = 0.000 (p < 0.05).